A rapid masking adhesive for thermal spraying and a method for preparing the same
Patent Information
- Application Number
- CN202611298165.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-13
AI Technical Summary
但现有遮蔽胶体系普遍存在诸多技术短板:一是常温固化周期过长,无法满足快速施工需求,严重制约生产效率;二是耐热性不足,针对温度为2000℃、速度为5马赫以上的喷涂焰流,材料易发生软化、流淌、碳化开裂甚至脱落,防护失效导致工件污染;三是附着力与可剥离性难以兼顾:附着力过强时,遮蔽胶虽在常温及高温焰流冲刷下贴附牢固、防护稳定,但喷涂后难以完整剥离,残胶较多,清理过程易划伤精密基材;附着力偏低时,虽剥离便捷、残胶极少,却易出现翘边,在高速粒子冲击下胶层会整片脱落,完全丧失遮蔽防护作用
[0017](2)超高耐温、抗高速焰流冲刷性能优异:氟改性有机硅基体搭配多层级隔热无机填料体系,可长期耐受≥2000℃焰流、5 马赫超音速熔融粒子持续冲刷;连续 10~20 次喷涂循环,胶层无软化流淌、无碳化开裂、无整块脱落,遮蔽防护稳定可靠,杜绝漏喷渗喷报废。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal spraying auxiliary materials technology, specifically relating to a thermal spraying rapid masking adhesive and its preparation method. Background Technology
[0002] Thermal spraying is a surface treatment technology that involves heating and molten metals, ceramics, alloys, or other coating materials, and then depositing them onto the workpiece surface via a high-speed airflow to form a functional protective coating. With its advantages of wear resistance, corrosion resistance, and high-temperature resistance, it is widely used in high-end manufacturing fields such as aerospace, shipbuilding, machinery, and petrochemicals. Thermal spraying operations only coat designated areas of the workpiece; non-sprayed areas must be masked to prevent molten particles from adhering and contaminating the workpiece, causing dimensional errors and performance defects. The performance of the masking material directly affects the finished product accuracy and production efficiency.
[0003] Currently, thermal spraying masking methods mainly include two categories: mechanical masking and material masking. Mechanical masking often uses metal components such as metal baffles and tooling fixtures, which have good heat resistance, but poor adaptability. It is difficult to fit complex workpiece structures such as irregular curved surfaces, holes, and gaps, and is prone to defects such as missed spraying and flash. In addition, it is cumbersome to disassemble and assemble, has high customization costs, and weak versatility, making it unsuitable for high-efficiency production scenarios with multiple product categories and small batches. Material masking is the mainstream protection method for complex workpieces, mainly using masking paints and masking adhesives. However, existing masking adhesive systems generally suffer from several technical shortcomings: First, the room temperature curing cycle is too long, failing to meet the demands of rapid construction and severely restricting production efficiency. Second, their heat resistance is insufficient; when facing spraying flames at temperatures above 2000℃ and speeds above Mach 5, the material is prone to softening, flowing, carbonizing, cracking, or even detachment, leading to protective failure and workpiece contamination. Third, adhesion and peelability are difficult to balance: when adhesion is too strong, although the masking adhesive adheres firmly and provides stable protection under both room temperature and high-temperature flames, it is difficult to peel off completely after spraying, leaving more residue that can easily scratch delicate substrates during cleaning. When adhesion is too low, although peeling is convenient and leaves very little residue, it is prone to edge lifting, and the adhesive layer may peel off entirely under the impact of high-speed particles, completely losing its masking and protective function. Fourth, their sealing flexibility is insufficient, resulting in inadequate filling of fine gaps in the workpiece and a high rate of missed or seepage defects. Summary of the Invention
[0004] The purpose of this invention is to provide a thermal spray fast masking adhesive and its preparation method. It has advantages such as being environmentally friendly, easy to apply, curing in 10 minutes, having good density, moderate flexibility, a balance between adhesion and peelability, and being able to withstand spraying temperatures ≥2000℃ and 10-20 cycles of flame jets at speeds ≥5 Mach without carbonization, peeling, cracking, or damage, and achieving 100% removal.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention provides a thermal spraying rapid masking adhesive, which, by weight percentage, consists of the following components:
[0006] The main base resin is one or a mixture of several of the following in any proportion: fluorine-modified single-terminated vinyl silicone oil, fluorine-modified double-terminated vinyl silicone oil, fluorine-modified side-chain vinyl silicone oil, and fluorine-modified end-side-chain vinyl silicone oil, with a vinyl content of 0.2 to 0.4%.
[0007] The crosslinking agent is one or a mixture of several of the following in any proportion: fluorinated end-hydrogen-containing silicone oil, fluorinated side-hydrogen-containing silicone oil, and fluorinated end-side bifunctional hydrogen-containing silicone oil, with a hydrogen content of 0.6 to 1.2%.
[0008] The filler is one or more of the following: feldspar powder (500 mesh, 800 mesh, 1250 mesh, 3000 mesh), silica powder, aluminum oxide (80~100μm), aluminum hydroxide, magnesium hydroxide, and fumed silica (5nm, 10nm, 15nm, 20nm).
[0009] The pigment is: Component A is one or more of zirconium oxide, aluminum phosphate and zirconium silicate; Component B is one or more of cobalt blue, cobalt chromium blue and vanadium zirconium blue.
[0010] The additives are: a substrate wetting and dispersing agent selected from BYK-9076, BYK-163, BYK-111, and BYK-3764; a defoamer selected from BYK-A530, BYK-A550, BYK-1794, and BYK-055; a surface additive selected from BYK-3764, BYK-378, and BYK-3762; and an adhesion modifier selected from BYK-4509, BYK-4511, and BYK-358N.
[0011] The catalyst is one or two of the following: Karstedt catalyst, Speier catalyst, and Ashby catalyst.
[0012] The inhibitor is one or two of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hex-3-ol, and 1-ethynylcyclohexanol.
[0013] The second aspect provides a method for preparing a rapid masking adhesive that can be used for thermal spraying, comprising the following steps: Preparation of Component A: Fluorine-modified vinyl silicone oil was added to a planetary mixer and the mixture was stirred with pigments, fillers and additives. The mixture was then mixed for 30 min. Platinum catalyst was added and the mixture was vacuum stirred for 1 h to remove bubbles. After cooling and depressurization, the mixture was discharged to obtain Component A.
[0014] Preparation of Component B: Fluorine-modified vinyl silicone oil and fluorine-modified hydrogen-containing silicone oil were added to a planetary mixer and the mixture was stirred and then added with pigments, fillers and additives. The mixture was mixed for 30 min. Inhibitors were added and the mixture was vacuum stirred for 1 h to remove bubbles. After cooling and depressurization, the mixture was discharged to obtain Component B.
[0015] Instructions for use: Mix components A and B by hand in a 1:1 mass ratio until the color is uniform. Press and adhere the mixture to the surface of the metal component. After 5 minutes, the component can be thermally sprayed.
[0016] (1) Ultra-fast room temperature curing: The two components are mixed in a 1:1 ratio and set in 5 minutes and fully cured in 10 minutes. No heating or baking is required, which greatly shortens the waiting time before spraying and is suitable for continuous and rapid production on the production line. The curing efficiency is 3 to 8 times higher than that of traditional masking adhesives.
[0017] (2) Excellent resistance to ultra-high temperature and high-speed flame erosion: The fluorine-modified organosilicon matrix combined with the multi-level heat-insulating inorganic filler system can withstand the continuous erosion of flames at ≥2000℃ and supersonic molten particles at Mach 5 for a long time; after 10 to 20 consecutive spraying cycles, the adhesive layer does not soften or flow, does not carbonize or crack, and does not fall off in whole pieces. The shielding and protection are stable and reliable, and the leakage and seepage of the spraying are eliminated.
[0018] (3) Precise balance between adhesion and peelability: The adhesion modifier is combined with the fluorine-modified low surface energy structure. During the spraying process at room temperature and high temperature, the adhesive layer adheres tightly to the substrate, and the gaps are fully filled without lifting edges. After the spraying cools down, the entire sheet can be peeled off completely, with no residual adhesive on the substrate surface. No sanding or solvent wiping is required, avoiding scratches on the reference surface of precision parts and simplifying the post-processing procedures.
[0019] (4) Excellent flexibility and sealing and filling performance: The putty has good thixotropic properties and no dripping during construction; after curing, the adhesive layer is flexible and elastic, which can tightly fill micron-level fine gaps, threads, and irregular grooves, block the penetration of high-temperature molten particles, and greatly reduce the failure rate of seepage spraying.
[0020] (5) Stable storage, convenient construction, and green environmental protection: A and B single components can be stored at room temperature and away from light for 6 months without premature cross-linking; solvent-free formula, no volatile toxic organic matter; can be manually kneaded, suitable for various complex curved surfaces, small holes, thin-walled precision workpieces, replacing customized metal shielding fixtures, reducing the shielding cost per piece.
[0021] (6) Visual inspection of mixing ratio to prevent errors: Group A is white and Group B is blue. Mix them evenly before construction. Visually judge whether the mixing ratio meets the standard to avoid mixing imbalance leading to curing failure and poor protection. Detailed Implementation Example 1
[0022] Component A (parts by weight): 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.3%), 45 parts of feldspar powder (1250 mesh), 10 parts of alumina (90μm), 5 parts of fumed silica (10nm), 1.5 parts of zirconium oxide, 0.8 parts of BYK-9076, 0.5 parts of BYK-A530, 0.3 parts of BYK-3764, 0.4 parts of BYK-4509, and 0.02 parts of Karstedt catalyst.
[0023] Component B (parts by weight): 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.3%), 2.5 parts of fluorine-modified hydrogen-terminated silicone oil (hydrogen content 0.8%), 42 parts of feldspar powder (1250 mesh), 10 parts of aluminum oxide (90μm), 5 parts of fumed silica (10nm), 1.5 parts of cobalt blue, 0.8 parts of BYK-9076, 0.5 parts of BYK-A530, 0.3 parts of BYK-3764, 0.4 parts of BYK-4509, and 0.05 parts of 1-ethynylcyclohexanol.
[0024] Preparation method: Prepare components A and B separately according to the aforementioned general method. When using, mix them by hand in a 1:1 mass ratio until the color is uniform (white and blue are mixed to form a uniform light blue). Apply the mixture to the non-sprayed area of the aluminum alloy test plate, press and adhere it, set it at room temperature (25℃) for 5 minutes, and completely cure it in 10 minutes. Example 2
[0025] Component A (parts by weight): 30 parts of fluorine-modified side-chain vinyl silicone oil (vinyl content 0.2%), 30 parts of silica powder, 20 parts of aluminum hydroxide, 8 parts of fumed silica (5nm), 2 parts of aluminum phosphate, 1.0 part of BYK-163, 0.6 parts of BYK-1794, 0.3 parts of BYK-378, 0.5 parts of BYK-4511, and 0.01 parts of Speier catalyst.
[0026] Component B (parts by weight): 30 parts of fluorine-modified side-chain vinyl silicone oil (vinyl content 0.2%), 3 parts of fluorine-modified side-hydrogen silicone oil (hydrogen content 1.0%), 30 parts of silica powder, 18 parts of aluminum hydroxide, 8 parts of fumed silica (5nm), 2 parts of cobalt chromium blue, 1.0 part of BYK-163, 0.6 parts of BYK-1794, 0.3 parts of BYK-378, 0.5 parts of BYK-4511, and 0.08 parts of 2-methyl-3-butyn-2-ol.
[0027] The preparation and usage methods are the same as in Example 1. Example 3
[0028] Component A (parts by weight): 40 parts of fluorine-modified end-chain vinyl silicone oil (vinyl content 0.4%), 40 parts of feldspar powder (3000 mesh), 15 parts of magnesium hydroxide, 1 part of zirconium silicate, 0.8 parts of BYK-111, 0.4 parts of BYK-055, 0.3 parts of BYK-3762, 0.3 parts of BYK-358N, and 0.03 parts of Ashby catalyst.
[0029] Component B (parts by weight): 40 parts of fluorine-modified end-chain vinyl silicone oil (vinyl content 0.4%), 2 parts of fluorine-modified end-chain bifunctional hydrogen-containing silicone oil (hydrogen content 1.2%), 38 parts of feldspar powder (3000 mesh), 15 parts of magnesium hydroxide, 1.5 parts of vanadium zirconium blue, 0.8 parts of BYK-111, 0.4 parts of BYK-055, 0.3 parts of BYK-3762, 0.3 parts of BYK-358N, and 0.1 parts of 3,5-dimethyl-1-hex-3-ol.
[0030] The preparation and usage methods are the same as in Example 1. Example 4
[0031] Component A (parts by weight): 35 parts of a fluorine-modified single-terminated vinyl silicone oil (vinyl content 0.25%) and a fluorine-modified double-terminated vinyl silicone oil mixed in a 1:1 ratio; 50 parts of feldspar powder (800 mesh); 5 parts of fumed silica (20 nm); 1.5 parts of a 1:1 mixture of zirconium oxide and zirconium silicate; 0.7 parts of BYK-3764; 0.5 parts of BYK-A550; 0.3 parts of BYK-378; 0.5 parts of BYK-4509; and 0.02 parts of Karstedt catalyst.
[0032] Component B (parts by weight): 35 parts of a fluorinated mono-terminated vinyl silicone oil and a fluorinated double-terminated vinyl silicone oil mixed in a 1:1 ratio; 2.8 parts of a fluorinated end-hydrogen silicone oil (0.6% hydrogen content) and a fluorinated side-hydrogen silicone oil (0.9% hydrogen content) mixed in a 1:2 ratio; 45 parts of feldspar powder (800 mesh); 5 parts of fumed silica (20 nm); 1.5 parts of a 1:1 mixture of cobalt blue and cobalt chromium blue; 0.7 parts of BYK-3764; 0.5 parts of BYK-A550; 0.3 parts of BYK-378; 0.5 parts of BYK-4509; and 0.06 parts of 1-ethynylcyclohexanol.
[0033] The preparation and usage methods are the same as in Example 1.
[0034] Comparative Example 1 (without fluorine-modified components, ordinary vinyl silicone oil system) Component A: 35 parts of ordinary double-terminated vinyl silicone oil (non-fluorinated, vinyl content 0.3%), and the remaining fillers, additives and catalysts are the same as in Example 1.
[0035] Component B: 2.5 parts of ordinary hydrogen-containing silicone oil (non-fluorinated, hydrogen content 0.8%), the rest are the same as Component B in Example 1.
[0036] The preparation and usage methods are the same as in Example 1.
[0037] Comparative Example 2 (without adhesion modifier) Component A: BYK-4509 was removed in Example 1, and the rest remained unchanged.
[0038] Component B: BYK-4509 was removed in Example 1, and the rest remained unchanged.
[0039] The preparation and usage methods are the same as in Example 1.
[0040] Comparative Example 3 (Vinyl content too low: 0.1%, below the lower limit of this invention) Component A: 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.1%), the remaining fillers, pigments, additives and catalysts are completely consistent with Component A of Example 1.
[0041] Component B: 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.1%), 2.5 parts of fluorine-modified hydrogen-terminated silicone oil (hydrogen content 0.8%), and the remaining fillers, pigments, additives, and inhibitors are completely consistent with Component B of Example 1.
[0042] The preparation and usage methods are the same as in Example 1.
[0043] Comparative Example 4 (Vinyl content too high: 0.5%, exceeding the upper limit of this invention) Component A: 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.5%), the remaining fillers, pigments, additives and catalysts are completely consistent with Component A of Example 1.
[0044] Component B: 35 parts of fluorine-modified double-terminated vinyl silicone oil (vinyl content 0.5%), 2.5 parts of fluorine-modified hydrogen-terminated silicone oil (hydrogen content 0.8%), and the remaining fillers, pigments, additives, and inhibitors are completely consistent with Component B of Example 1.
[0045] The preparation and usage methods are the same as in Example 1.
[0046] Comparative Example 5 (crosslinking agent with too low hydrogen content: 0.4%, below the lower limit of this invention) Component A: Same as Component A in Example 1; Component B: 2.5 parts of fluorine-modified hydrogen-containing silicone oil (0.4% hydrogen content), the remaining components are completely consistent with Component B of Example 1.
[0047] The preparation and usage methods are the same as in Example 1.
[0048] Comparative Example 6 (crosslinking agent with excessive hydrogen content: 1.5%, exceeding the upper limit of this invention) Component A: Same as Component A in Example 1; Component B: 2.5 parts of fluorine-modified hydrogen-containing silicone oil (1.5% hydrogen content), the remaining components are completely consistent with Component B of Example 1.
[0049] The preparation and usage methods are the same as in Example 1.
[0050] Comparative Example 7 (the matrix resin was replaced with a fluorine-modified single-terminated vinyl silicone oil single resin) Component A: 35 parts of fluorine-modified single-terminated vinyl silicone oil (vinyl content 0.3%), and the remaining fillers, pigments, additives, and catalysts are the same as in Example 1A; Component B: 35 parts of fluorine-modified single-terminated vinyl silicone oil (vinyl content 0.3%), 2.5 parts of fluorine-modified hydrogen-terminated silicone oil (hydrogen content 0.8%), and the remaining fillers, pigments, additives, and inhibitors are the same as in Example 1B.
[0051] The preparation and usage methods are the same as in Example 1.
[0052] Comparative Example 8 (Crosslinking agent is solely fluorine-modified hydrogen-containing silicone oil with a hydrogen content of 0.8%) Component A: Same as Component A in Example 1; Component B: 2.5 parts of fluorine-modified hydrogen-containing silicone oil (0.8% hydrogen content), the remaining components are completely consistent with Component B of Example 1.
[0053] The preparation and usage methods are the same as in Example 1. Performance testing
[0054] The masking adhesives prepared in Examples 1-4 and Comparative Examples 1-8 were applied to the non-sprayed areas of a stainless steel test plate (100mm×100mm×3mm) with a thickness of 3mm. After curing at room temperature for 10 minutes, the following tests were performed: 1. Appearance and condition: Under natural light, components A and B are visually inspected. The putty has a fine and uniform texture with no visible impurities.
[0055] 2. Density: The density of the mixed adhesive compound was tested according to GB / T 13354-2017 "Determination of density of liquid adhesives by weight cup method".
[0056] 3. Manual operation time (operable time): At 25℃, start timing when manually kneading and mixing components A and B in a 1:1 ratio. Record the time until the material loses its plasticity and can no longer be kneaded and coated. This is the operable time.
[0057] 4. Curing time: At room temperature of 25℃, after mixing and coating, the time is considered complete when the adhesive layer is no longer sticky to the touch and there is no indentation or deformation when pressed.
[0058] 5. Shore A Hardness: The Shore A hardness of a 2mm thick fully cured film was tested according to GB / T 531.1-2019 "Test Method for Indentation Hardness of Vulcanized Rubber or Thermoplastic Rubber".
[0059] 6. Tensile strength and elongation at break: Type I specimens were prepared for testing in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0060] 7. Tear strength: Tested according to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)" using right-angled specimens.
[0061] 8. High temperature and erosion of heat-resistant spraying flame: Supersonic flame spraying equipment, flame temperature ≥2000℃, flame velocity ≥5 Mach; one spraying time is 1 minute, cooling to room temperature is one cycle, 20 or more consecutive cycles, observe the powdering, peeling and cracking of the adhesive layer.
[0062] 9. Peelability: After completing the thermal spraying cycle and cooling to room temperature, manually peel off the adhesive layer; evaluate residual adhesive by visual inspection and weighing; observe whether there are scratches or corrosion marks on the substrate surface.
[0063] 10. Storage period: Components A and B should be sealed and stored in a light-protected environment at 35°C. Open the lid periodically to check for gelation, clumping, or premature cross-linking, and record the longest acceptable storage time.
[0064] The test results are shown in Table 1: Table 1. Performance test results of the examples and comparative examples.
[0065]
[0066]
[0067]
[0068] Results Analysis: The test data in the table show that, in Examples 1-4 of this invention, the vinyl content of the fluorinated modified vinyl silicone oil was controlled at 0.2-0.4%, the hydrogen content of the fluorinated modified hydrogen crosslinking agent was controlled at 0.6-1.2%, a compounded fluorinated modified silicone oil matrix was used, combined with an adhesion modifier and multi-stage compounded inorganic fillers, supplemented by a matched catalyst-inhibitor synergistic system, all meeting the technical specifications of the product: manual workability time 6.2-6.8 min ≥ 5 min, complete curing time 10 min ≤ 10 min; Shore A hardness 43-49, tensile strength 4.0-4.4 MPa, elongation at break 262%-294%, tear strength 74-81 kN / m, indicating sufficient mechanical properties; density 1.18-1.24 g / cm³ falling within the range of 1.2 ± 0.3 g / cm³; after 15 cycles at ≥2000℃ and 5... After being circulated and washed by a Mach-speed supersonic flame, the carbonization depth of the adhesive layer is 0, and the peeling area is 0%. The adhesion by the pull-out method is maintained within a reasonable range of 1.35-1.48MPa, ensuring that the adhesive layer adheres firmly and without lifting edges during high-temperature spraying, and can be completely peeled off after cooling, with a substrate residual adhesive mass ratio of 0, achieving 100% removal without substrate damage. The gap penetration area ratio is 0, which can fully fill micro-gaps and prevent seepage and leakage. The adhesive layer does not crack under a bending diameter of 10mm, with a thixotropic index of 4.3-5.1, and the putty has excellent anti-sagging construction performance. The shelf life can reach 12 months at 35℃. It is a single component without gelation or premature cross-linking, and its performance in terms of process, mechanical properties, heat resistance, and storage is balanced and unified.
[0069] Each comparative example deviated from the scope of protection of this invention due to factors such as the type of matrix resin, vinyl content, hydrogen content of crosslinking agent, and lack of functional additives. One or more technical indicators failed to meet the requirements. Specific analysis is as follows: Comparative Example 1 (without fluorine-modified matrix resin) The substrate uses ordinary non-fluorinated modified vinyl silicone oil, lacking the thermal stability and low surface energy effect inherent in fluorine structures. Mechanical properties are significantly reduced: tensile strength (2.6 MPa) and tear strength (52 kN / m) are below the required specifications; curing time is extended to 15 minutes; after 15 cycles of thermal spraying, the edge carbonization depth is 0.42 mm, and the peeling area is 21%; the elongation at break is only 164%, and cracking occurs during bending tests; the residual adhesive content in the substrate is 2.7%, and the gap penetration area is 12.4%. This indicates that a fluorinated modified silicone oil substrate is fundamental for masking adhesives to achieve high-temperature erosion resistance, high toughness, and low residue; ordinary silicone substrates cannot simultaneously meet the stringent requirements of thermal spraying.
[0070] Comparative Example 2 (Removal of Adhesion Modifier) The rest of the formulation remained unchanged, except for the removal of the adhesion modifier. The adhesion strength using the pull-off method dropped to 0.71 MPa. Although the residual adhesive was zero and the mechanical properties were basically up to standard, the adhesive layer edges curled up under the action of the high-temperature flame, and the gap penetration area reached as high as 31.7%, resulting in the failure of masking and protection. This proves that the adhesion modifier plays a crucial synergistic regulatory role, achieving a performance balance of "firm adhesion under high-temperature conditions and complete and easy peeling after cooling." The absence of this component would directly cause the spray coating to seep through and become unusable.
[0071] Comparative Example 3 (vinyl content 0.1%, below the lower limit of 0.2%) The resin has insufficient crosslinking reaction sites and a low crosslinking density. The manual workable time reaches 11 minutes, and the complete curing time is 22 minutes, exceeding the curing time specifications. The Shore A hardness is 31, tensile strength is 2.1 MPa, and tear strength is 44 kN / m, all mechanical properties failing to meet standards. After high-temperature spraying, the adhesive layer softens and blisters, with a peeling area of 33% and a carbonization depth of 0.31 mm. The gap penetration area is 26.3%, indicating a significant deterioration in high-temperature protection. This indicates that the vinyl content is too low, the crosslinking network construction is insufficient, and the adhesive layer strength and heat resistance cannot meet the requirements of thermal spraying conditions.
[0072] Comparative Example 4 (vinyl content 0.5%, higher than the upper limit of 0.4%) Excessive crosslinking sites and high crosslinking density lead to a hard and brittle adhesive layer. The workable time is shortened to 3.2 minutes, resulting in insufficient application window. The Shore A hardness of 58 is too high, with an elongation at break of only 141%, and cracking occurs during bending tests. The tensile strength of 5.7 MPa and tear strength of 96 kN / m are also too high, causing the adhesive layer to crumble upon peeling, leaving 4.8% adhesive residue on the substrate. The shelf life at 35°C is only 8 months, indicating decreased storage stability. This demonstrates that while a high vinyl content results in faster curing and increased strength, it sacrifices toughness, peelability, and storage stability, making it unsuitable for masking precision workpieces.
[0073] Comparative Example 5 (crosslinking agent with hydrogen content of 0.4%, below the lower limit of 0.6%) The crosslinking agent lacks sufficient active hydrogen groups, resulting in incomplete crosslinking. Manual operation time was 13 minutes, and complete curing time was 25 minutes, far exceeding the technical specifications. Mechanical properties were severely inadequate, with a Shore A hardness of 28, tensile strength of 1.8 MPa, and tear strength of 37 kN / m. After thermal spraying, the adhesive layer melted and flowed, with a 47% peeling area, a carbonization depth of 0.63 mm, and a gap penetration area of 44.1%, indicating a near-complete failure of its masking function. This demonstrates that the crosslinking agent's insufficient hydrogen content prevents the formation of a complete and effective crosslinked elastic network, thus failing to withstand the impact of high-temperature, high-speed particles.
[0074] Comparative Example 6 (crosslinking agent with hydrogen content of 1.5%, higher than the upper limit of 1.2%) Excessive active hydrogen groups result in excessively high crosslinking density. The workable time is only 3.0 minutes, insufficient for application; the Shore A hardness of 56 is too high, and the elongation at break is 133%, making the adhesive layer brittle and prone to bending and cracking; the adhesive layer crumbles during peeling, with a residual adhesive ratio of 3.1%; the shelf life at 35℃ is only 7 months, indicating a tendency for premature crosslinking. Excessive hydrogen content in the crosslinking agent leads to loss of adhesive layer toughness and shortened shelf life, also failing to meet product usage requirements.
[0075] Comparative Example 7 (using only a single fluorine-modified single-terminated vinyl silicone oil as the matrix) Using only a single-end-capped resin resulted in asymmetrical molecular reaction sites and poor uniformity of the crosslinking network. The curing time was extended to 12 minutes; after thermal spraying, the edges curled up, with an 8% peeling area and a 6.8% crevice penetration area; the tear strength was 66 kN / m, slightly below the technical threshold. This indicates that the crosslinking network integrity of a single-type matrix resin is insufficient, and compounding with multiple fluorinated modified vinyl silicone oils is more conducive to obtaining a masking adhesive with excellent overall performance.
[0076] Comparative Example 8 (Crosslinking agent only used fluorine-modified hydrogen-containing silicone oil) Crosslinking sites are concentrated on the molecular side chains, with insufficient crosslinking at the molecular chain ends. The tear strength is 69 kN / m, slightly lower than the 70 kN / m target. After thermal spraying, localized fine cracks appeared in the adhesive layer, with a crack penetration area of 4.3%. Compared with the combined crosslinking system of terminal hydrogen and side hydrogen, the adhesive layer obtained by crosslinking with hydrogen-containing silicone oil on only one side has shortcomings in its resistance to particle impact and penetration.
[0077] In summary, only the fluorinated modified vinyl silicone oil matrix (vinyl 0.2-0.4%) and fluorinated modified hydrogen-containing crosslinking agent (hydrogen 0.6-1.2%) specified in this invention, combined with adhesion modifiers, multi-level compound fillers, and a catalyst-inhibitor synergistic system, can achieve the synergistic effect of various components and parameter ranges, simultaneously realizing multiple mutually restrictive technical effects such as a suitable manual operation window, rapid room temperature curing, excellent mechanical toughness, resistance to ≥2000℃, Mach 5 flame erosion, complete peeling without residue, low penetration, and long shelf life. The absence of any key component in the formulation or deviation of parameters from the scope of protection of this invention will result in at least one or more key technical indicators failing to meet the requirements. This demonstrates that the selection of formulation components and the limitation of parameter ranges in this invention cannot be obtained through simple, limited experiments, and possesses non-obvious inventiveness.
[0078] Industrial Applicability: The masking adhesive provided by this invention is in putty form, allowing for manual shaping. It is suitable for various complex irregular surfaces, deep holes, threads, and other structures, eliminating the need for customized metal tooling and significantly reducing masking costs. Its solvent-free formula meets environmental protection requirements, and the color difference between the two components facilitates visual assessment of mixing uniformity. It is suitable for large-scale application in the thermal spraying production of precision components such as aero-engine blades, ship propellers, and oil valves.
Claims
1. A thermal spraying rapid masking adhesive, characterized in that, Composed of component A and component B, by mass percentage: Component A includes: Main base material resin 30-40%; Filler content: 50-60%; Pigment 1-2%; Additives 1-2%; Catalyst 0.01–0.03%; Component B includes: Main base material resin 30-40%; Crosslinking agent 2-3%; Filler content: 45-55%; Pigment 1-2%; Additives 1-2%; Inhibitors: 0.01%–0.1%.
2. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The main base resin is selected from one or more of fluorine-modified single-terminated vinyl silicone oil, fluorine-modified double-terminated vinyl silicone oil, fluorine-modified side-chain vinyl silicone oil and fluorine-modified end-side-chain vinyl silicone oil, and the vinyl content is 0.2 to 0.4 wt%.
3. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The crosslinking agent is one or a mixture of several of the following in any proportion: fluorinated end-hydrogen-containing silicone oil, fluorinated side-hydrogen-containing silicone oil, and fluorinated end-side bifunctional hydrogen-containing silicone oil, with a hydrogen content of 0.6 to 1.2%.
4. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The filler is one or more of feldspar powder, silica powder, aluminum oxide, aluminum hydroxide, magnesium hydroxide, and fumed silica.
5. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The pigment consists of component A, which is one or more of zirconium oxide, aluminum phosphate, and zirconium silicate; and component B, which is one or more of cobalt blue, cobalt chromium blue, and vanadium zirconium blue.
6. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The additives are: substrate wetting and dispersing agents, one or more of BYK-9076, BYK-163, BYK-111 and BYK-3764; defoamers, one or more of BYK-A530, BYK-A550, BYK-1794 and BYK-055; surface additives, one or more of BYK-3764, BYK-378 and BYK-3762; and adhesion modifiers, one or more of BYK-4509, BYK-4511 and BYK-358N.
7. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The catalyst is one or two of the following: Karstedt catalyst, Speier catalyst, and Ashby catalyst.
8. The thermal spraying rapid masking adhesive according to claim 1, characterized in that, The inhibitor is one or two of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hex-3-ol, and 1-ethynylcyclohexanol.
9. A method for preparing a thermal spraying rapid masking adhesive as described in any one of claims 1 to 8, characterized in that, Includes the following steps: Preparation of Component A: Add the main base resin to a planetary mixer and press, start the mixer and add pigments, fillers and additives, mix for 30 min; add catalyst, vacuum mix for 1 h to degas, cool and depressurize and discharge to obtain Component A; Preparation of Component B: In a planetary mixer press, add the main base resin and crosslinking agent, start stirring and add pigments, fillers and additives, and mix for 30 min; add inhibitor, vacuum stir for 1 h to degas, and discharge after cooling and depressurization to obtain Component B.
10. A method of using a thermal spraying rapid masking adhesive as described in any one of claims 1 to 8, characterized in that, Mix components A and B by hand in a 1:1 mass ratio until the color is uniform. Press and adhere the mixture to the surface of the metal component. After 5 minutes, the component can be thermally sprayed.